2007
DOI: 10.1097/inf.0b013e31806166bb
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mediastinitis Following Median Sternotomy in Children

Abstract: The presence of a known or possible genetic syndrome, American Society of Anesthesiologists score >3, and the presence of intracardiac pacing wires for >3 days were each associated with the development of mediastinitis in children after median sternotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
0
20
0
4
Order By: Relevance
“…In one of the largest series documenting the risk factors for developing postoperative mediastinitis in children, Kagen et al found that only the presence of a genetic syndrome, an American Society of Anesthesiologists score of >3, and the presence of intracardiac pacing wires for >3 days were statistically significant. [15] None of the children in our series developed mediastinitis, and in none were mediastinal drains left in situ.…”
Section: Resultsmentioning
confidence: 99%
“…In one of the largest series documenting the risk factors for developing postoperative mediastinitis in children, Kagen et al found that only the presence of a genetic syndrome, an American Society of Anesthesiologists score of >3, and the presence of intracardiac pacing wires for >3 days were statistically significant. [15] None of the children in our series developed mediastinitis, and in none were mediastinal drains left in situ.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the preoperative factors that are generally believed to affect SSIs include newborns aged <1 month, infants aged <1 year, duration of preoperative hospitalization ≥48 h, and genetic syndromes. 8,12,14,15) In terms of the preoperative attributes of the patients in this study, patients in Group R were younger than those in Group E, with significantly lower height, weight and body surface area (Table 1). Despite this, the occurrence of SSIs and mediastinitis was reduced in Group R. This indicates that the efficacy of our SSI prevention measures outweighed the disadvantage of small body size.…”
Section: Discussionmentioning
confidence: 99%
“…26 Different risk factors that may predispose children for mediastinitis, such as wound contamination at the time of surgical procedure, prolonged surgical times, younger age, use of deep hypothermia, and a higher American Society of Anesthesiologists score, have been reported. 27 Kagan and colleagues 27 looked at the risk factors for mediastinitis after median sternotomy in children. They demonstrated that an American Society of Anesthesiologists score of 4 or greater, duration of epicardial pacing wires greater than 3 days, and a known or a possible genetic syndrome or chromosomal abnormality were risk factors that were associated with the development of mediastinitis.…”
Section: Complicationsmentioning
confidence: 99%